Assessing students’ satisfaction towards agricultural learning services of the Royal Flora Ratchaphruek - Homhuan, O.,; Panpakdee, C.,; Borisutdhi, Y., (International Journal of Agricultural Technology, 2021)
The major findings revealed the students’ mean satisfaction level to be 4.33 out of the 5.00 maximum score, interpreted as they were very satisfied. This high satisfaction is because of the excellence of learning courses and services provided by the Royal Flora Ratchaphruek that can fulfill the students’ goals. The attending students stated their knowledge has enhanced with the up-to-date course contents applicable in daily life. Also, the altruistic and liberal nature of the instructors was considered being a beneficial and motivating factor for students to communicate both questions and ideas. However, the independent sample t-test revealed the statistically significant difference between male and female informants in terms of the mean value of satisfaction towards such agricultural learning services for the p-value < 0.05. Most means were found not statistically significantly different. Thus, this type of learning services should be established to inspire children to interest in agriculture. But edutainment’s components such as attractive environments and enjoyable activities similar to the Royal Flora Ratchaphruek’s must be integrated into the program. These components are vital not only get children to engage throughout the learning process but also let them explore the actual world of agriculture